The silent governess eaudiobook - Klassen, Julie (Recorded Books Inc., 2014)
With the stunning prose and engaging characters of The Silent Governess, Christy Award finalist Julie Klassen whisks listeners away to Regency England for a compelling tale of romance and intrigue. Thinking she's guilty of a crime, Olivia Keene flees her home and stumbles upon a grand estate-and a damaging secret. To ensure her silence, Lord Bradley insists she serve in his opulent manor. "Klassen expertly infuses her . inspirational tale with a gothic atmosphere, resulting in a sweetly intriguing romance worthy of Victoria Holt."-Booklist